2016
DOI: 10.1136/medethics-2016-103543
|View full text |Cite
|
Sign up to set email alerts
|

The role of law in decisions to withhold and withdraw life-sustaining treatment from adults who lack capacity: a cross-sectional study

Abstract: Medical specialists prioritise patient-related clinical factors over law when confronted with a scenario where legal compliance is inconsistent with what they believe is clinically indicated. Although legally knowledgeable specialists were more likely to comply with the law, compliance in the scenario was not motivated by an intention to follow law. Ethical considerations (which are different from, but often align with, law) are suggested as a more important influence in clinical decision-making. More educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 27 publications
3
27
0
Order By: Relevance
“…Elsewhere we have identified significant gaps in doctors’ legal knowledge [ 11 ] but increasing knowledge is not sufficient, in and of itself, to lead to compliance with law. It is also necessary for the role, utility and relevance of law to be understood [ 12 ] and acted upon. That said, increasing knowledge may have an effect on compliance where the law in question is counterintuitive and/or inconsistent with widely held views in the medical profession and with accepted ethical positions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elsewhere we have identified significant gaps in doctors’ legal knowledge [ 11 ] but increasing knowledge is not sufficient, in and of itself, to lead to compliance with law. It is also necessary for the role, utility and relevance of law to be understood [ 12 ] and acted upon. That said, increasing knowledge may have an effect on compliance where the law in question is counterintuitive and/or inconsistent with widely held views in the medical profession and with accepted ethical positions.…”
Section: Discussionmentioning
confidence: 99%
“…It is part of a three-year study which has considered the role of law in decisions to withhold or withdraw life-sustaining treatment from adults who lack capacity. Previous papers from this study have examined issues such as whether doctors know the law in this area [ 11 ], whether legally knowledgeable doctors are more likely to follow the law [ 12 ], and the role of law for palliative care specialists, including their part in advancing end-of-life legal knowledge as a trusted source of information for other doctors, nurses, patients and families [ 13 ]. The focus of the present paper is a natural experiment which tests the impact of critical differences in end-of-life law across three Australian jurisdictions: New South Wales (NSW), Victoria and Queensland.…”
Section: Introductionmentioning
confidence: 99%
“…A 2007 study found that the presence of an ACD did not influence healthcare providers’ decisions in using life-sustaining treatments or initiating comfort care plans 12. More recently, Australian researchers presented doctors from New South Wales and Victoria with a hypothetical case scenario to investigate compliance with ACDs 13. In responding to the scenario, only 32% of doctors reported that they would adhere to the ACD in accordance with the law.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several studies have pointed to a lack of knowledge regarding living wills among health professionals, as opposed to positive attitudes towards the document [16][17][18][19] , with a direct relationship between the level of knowledge and characteristics such as previous experience and academic education 18,19 . Likewise, procedures that do not comply with end-oflife legislation have already been associated with a lack of familiarity with these legal principles 20 .…”
Section: Discussion Of Resultsmentioning
confidence: 99%